The Effects of Growing Media Composition and Trichoderma sp. Against The Growth and The Yield of Javanese Ginseng Plant (Talinum paniculatum Geartn.) - Cintya Mareta Putri Nasir; Saiful Arifin; M Abror (Universitas Muhammadiyah Sidoarjo, 2022)
This research has made a goal to know the interaction between growing media and Trichoderma sp. and their impact for the growth and production of Javanese Ginseng (Talinum paniculatum Geartn.) This research was carried out in February-May 2022 on the land of Boro Village, Tanggulangin using polybags. The study employs Randomized Block Design with two trial factors. The 1st factor is growing media. Top Soil 100%; Top Soil 50% + Sand 50%; Top Soil 50% Sand 25% + Charcoal Chaff 25%; Top Soil 50% + Sand 25% + Cocopeat 25%. For the 2 nd Factor is Trichoderma sp. Without Trichoderma sp. and with 20ml Trichoderma sp. These 8 combinations of treatment, repeated 3 times. The observed variable is the height of the plant, the number of the leaves, diameter of the stem, the number of the shoots, the weight of the leaf and length of the plant roots. The results showed that between the treatment of growing media composition and Trichoderma sp. there is no real impact on all observation variables. The treatment of growing media composition has a noticeable effect on the height, number of leaves and number of shoots of the Javanese Ginseng plant. The treatment of composition between soil and sand produces the highest plants with the heaviest leaves. While the treatment of giving Trichoderma sp. has an unreal effect on all variables